De la ilegibilidad de lo ajeno. lectura mágica y escritura mimética en Alfred Döblin - Sven Werkmeister (Antípoda: Revista de Antropología y Arqueología, 2012)
The article discusses and questions the concept of "cultural text" developed by anthropologists such as Clifford Geertz. The theory of culture as text opens the possibility of a semiotic reading of the cultural text, giving the anthropologist the role of hermeneutic interpreter of foreign cultures as systems of symbols. The paper shows, through analysis the literary of trilogy Amazons from German writer Alfred Dóblin, that the ethnographic approach is not always characterized by processes of understanding and interpretation, but is just the reflection of illegibility phenomena can be a fruitful basis for a cultural approach.